Tensile fatigue behavior of fiber-reinforced cementitious material with high ductility: Experimental study and novel P-S-N model - Huang, Bo-Tao; Li, Qing-Hua; Xu, Shi-Lang; Zhou, Bao-Min (Construction & building materials, 2018)
•The stress-control tensile fatigue behavior of UHTCC is investigated.•Four stages were observed in the evolution curve of fatigue deformation.•Smooth and rough areas can be distinguished on the fatigue failure surfaces.•Novel P-S-N models based on a modified S-N relation are proposed.•Using high-strength high-modulus fibers to replace partial PVA fibers in UHTCCs may improve the fatigue performance. Fiber-reinforced cementitious material with high ductility is a cement-based material with strain-hardening behavior under tension, and has potential application in structures sustaining fatigue loads. In this study, the tensile fatigue behavior of this material at various stress levels (S = 0.90, 0.85, 0.80, 0.75, 0.70, and 0.65) is investigated with the stress ratio of 0.1. The fatigue crack pattern, deformation, failure surfaces, and fiber failure modes are analyzed. Four stages are observed in the evolution curve of fatigue deformation. This is different from the three-stage curve of conventional concrete. “Smooth” and “rough” areas are distinguished on the fatigue failure surfaces with different fiber failure modes. Emphasis is placed on the development of a novel probabilistic model. On the basis of the initial distribution of static strength, P-S-N (probability of failure-stress level-fatigue life) models are proposed for a reliable application of this material. Moreover, a suggestion to improve the fatigue life of this material at low stress levels is provided.